2022
DOI: 10.3389/fphar.2022.987695
|View full text |Cite
|
Sign up to set email alerts
|

Better detoxifying effect of ripe forsythiae fructus over green forsythiae fructus and the potential mechanisms involving bile acids metabolism and gut microbiota

Abstract: Forsythiae Fructus (FF), the fruit of Forsythia suspensa (Thunb.) Vahl. (Lianqiao), is one of the most fundamental herbs in Traditional Chinese Medicines (TCM), mainly due to its heat-clearing and detoxifying effects. There are two types of FF, the greenish fruits that start to ripen (GF) and the yellow fruits that are fully ripe (RF), called “Qingqiao” and “Laoqiao” referred to the Chinese Pharmacopoeia, respectively. It undergoes a complex series of changes during the maturation of FF. However, the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…One study revealed that ripe fruits are better in detoxifying effect than green ones and the potential mechanisms involve bile acid metabolism and gut microbiota. 20 It is also reported that ripe fruits have more phillygenin than green ones and may be more suitable for treating cancers. 21 Unfortunately, except for a few studies, the clinical effects of ripe and green fruits are not correlated with active ingredients because of the lack of ingredient variation data.…”
Section: Mass Spectrometry Imaging (Msi) Can Either Identify New Compo-mentioning
confidence: 99%
See 1 more Smart Citation
“…One study revealed that ripe fruits are better in detoxifying effect than green ones and the potential mechanisms involve bile acid metabolism and gut microbiota. 20 It is also reported that ripe fruits have more phillygenin than green ones and may be more suitable for treating cancers. 21 Unfortunately, except for a few studies, the clinical effects of ripe and green fruits are not correlated with active ingredients because of the lack of ingredient variation data.…”
Section: Mass Spectrometry Imaging (Msi) Can Either Identify New Compo-mentioning
confidence: 99%
“…However, there are also evidences that support the usage of ripe fruits. One study revealed that ripe fruits are better in detoxifying effect than green ones and the potential mechanisms involve bile acid metabolism and gut microbiota 20 . It is also reported that ripe fruits have more phillygenin than green ones and may be more suitable for treating cancers 21 .…”
Section: Introductionmentioning
confidence: 99%